Status and Development Trends of Integrated IGBT Power Assembly - JIANG Yunfu; HUANG Nan; YUAN Yong; CHEN Yanping; SHI Tingchang (Kongzhi Yu Xinxi Jishu)
It summarized three technical methods that could improve the integration level of integrated IGBT power assembly, which included the novel thermal design, packaging and interconnection and driver & control circuit integration. The current technology classification was analyzed. Furthermore, the development trends of IGBT power assembly were discussed, including high intelligent design and PEBB module design.